Cyber Warfare - Truth, Tactics, and Strategies - Cunningham, Chase; Touhill, Gregory (Packt Publishing, 2020)
Insights into the true history of cyber warfare, and the strategies, tactics, and cybersecurity tools that can be used to better defend yourself and your organization against cyber threat. Key Features Define and determine a cyber-defence strategy based on current and past real-life examples Understand how future technologies will impact cyber warfare campaigns and society Future-ready yourself and your business against any cyber threat Book Description The era of cyber warfare is now upon us. What we do now and how we determine what we will do in the future is the difference between whether our businesses live or die and whether our digital self survives the digital battlefield. Cyber Warfare - Truth, Tactics, and Strategies takes you on a journey through the myriad of cyber attacks and threats that are present in a world powered by AI, big data, autonomous vehicles, drones video, and social media. Dr. Chase Cunningham uses his military background to provide you with a unique perspective on cyber security and warfare. Moving away from a reactive stance to one that is forward-looking, he aims to prepare people and organizations to better defend themselves in a world where there are no borders or perimeters. He demonstrates how the cyber landscape is growing infinitely more complex and is continuously evolving at the speed of light. The book not only covers cyber warfare, but it also looks at the political, cultural, and geographical influences that pertain to these attack methods and helps you understand the motivation and impacts that are likely in each scenario. Cyber Warfare - Truth, Tactics, and Strategies is as real-life and up-to-date as cyber can possibly be, with examples of actual attacks and defense techniques, tools. and strategies presented for you to learn how to think about defending your own systems and data. What you will learn Hacking at scale - how machine learning (ML) and artificial intelligence (AI) skew the battlefield Defending a boundaryless enterprise Using video and audio as weapons of influence Uncovering DeepFakes and their associated attack vectors Using voice augmentation for exploitation Defending when there is no perimeter Responding tactically to counter-campaign-based attacks Who this book is for This book is for any engineer, leader, or professional with either a responsibility for cyber security within their organizations, or an interest in working in this ever-growing field.